The power of learning styles memacu anak melejitkan prestasi dengan mengenali gaya belajarnya Barbara Prashnig;penerjemah,Nina Fauziah;Penyunting,Rahmani Astuti - PRASHNIG, Barbara; Fauziah, Nina; Astuti, Rahmani (2007)
367 hlm ilus 29 cm